Strategy Of The General Election Commission (Kpu) In Increasing Community Participation In The 2019 Elections In Gowa District - Ahmad (Journal AGENCY, 2021)
The purpose of this research is to find out the KPU's strategy in increasing public participation in the general election, and to find out what obstacles often occur in elections and how the solutions are carried out by the KPU, and also to analyze public participation in the General Elections Commission (KPU). Data collection techniques namely documentation and interviews. The type of research used is a research method using a qualitative approach based on theory and philosophy while the nature of this research is descriptive. The results of the research obtained by the author in the strategy of the KPU general election commission in increasing public participation in the general election in Gowa district in 2019 regarding the obstacles that are often experienced by the KPU and the KPU's strategy in increasing public participation, related to the KPU's strategy in increasing public participation has reached almost to all locations, both lowlands and highlands, related to the obstacles faced by the KPU during the election, it was returned to the people themselves to be more concerned about the importance of voting rights to be used, and also the hope that the public could reject money politics